Disruption and Overexpression of the Gene Encoding ACC (1-Aminocyclopropane-1-Carboxylic Acid) Deaminase in Soil-Borne Fungal Pathogen Verticillium dahliae Revealed the Role of ACC as a Potential Regulator of Virulence and Plant Defense - Tsolakidou, Maria Dimitra; Pantelides, Iakovos S; Tzima, Aliki K.; Kang, Seogchan; Paplomatas, Epaminondas J.; Tsaltas, Dimitrios (My University, 2019)
It has been suggested that some microorganisms, including plant growth-promoting rhizobacteria, manipulate the level of ethylene in plants by degrading 1-aminocyclopropane-1-carboxylic acid (ACC), an ethylene precursor, into α-ketobutyrate and ammonia, using ACC deaminase (ACCd). Here, we investigated whether ACCd of Verticillium dahliae, a soil-borne fungal pathogen of many important crops, is involved in causing vascular wilt disease. Overexpression of the V. dahliae gene encoding this enzyme, labeled as ACCd, significantly increased virulence in both tomato and eggplant, while disruption of ACCd reduced virulence. Both types of mutant produced more ethylene than a wild-type (70V-WT) strain, although they significantly differed in ACC content. Overexpression strains lowered ACC levels in the roots of infected plants, while the amount of ACC in the roots of plants infected with deletion mutants increased. To test the hypothesis that ACC acts as a signal for controlling defense, roots of WT and Never-ripe (Nr) tomato plants were treated with ACC before V. dahliae inoculation. Plants pretreated with ACC displayed less severe symptoms than untreated controls. Collectively, our results suggest a novel role of ACC as a regulator of both plant defense and pathogen virulence.
Keywords: V. dahliae ACCd gene; Verticillium dahliae